Investigating the Effects of Operational Factors on Wear Properties of Heat-Treated Pultruded Kenaf Fiber-Reinforced Polyester Composites using Taguchi Method - Boon Peng Chang; Wai Hoe Chan; Mohd Hafiz Zamri; Hazizan Md Akil; Hun Guan Chuah (Journal of Natural Fibers, 2019)
This study investigated the mechanical and wear properties of heat-treated pultruded kenaf fiber-reinforced polyester composites (PKFPCs) using pultrusion technique. A total of three heat treatment temperatures (120, 140, and 170°C) of PKFPC and untreated PKFPC were produced and their performance was compared. Different sliding conditions and different heat treatment temperatures on PKFPC were tested according to the Taguchi orthogonal array design of experiment. The worn surfaces and transfer films produced were examined using scanning electron microscopy. The results showed that PKFPC with a 140°C heat treatment exhibited better wear performance than untreated PKFPC and PKFPC with 120 and 170°C heat treatments. The flexural strength and modulus of PKFPC increased after heat treatment. The counterface roughness and heat treatment temperature are the most significant factors affecting the wear performance of PKFPC. The optimum sliding conditions to achieve lowest wear and friction in the tested operating environment were determined.